(untitled) (Intent Research Scientific Journal, 2023)
The resistance of the organism to adverse environmental factors in the process of adaptation, after the reconstruction of ventilation systems and to new floor structures, where humoral protection factors play a significant role, has been established, which allows a fairly complete and objective assessment of the state of natural stability. ¬ti calves during the hot periods of the year.